JavaScript essentials - McFedries, Paul (For Dummies, 2024)
The concise and digestible get-started guide to JavaScript programming JavaScript Essentials For Dummies is your quick reference to all the core concepts about JavaScript--the dynamic scripting language that is often the final step in creating powerful websites. This no-nonsense book gets right to the point, eliminating review material, wordy explanations, and fluff. Find out all you need to know about the foundations of JavaScript, swiftly and crystal clear. Perfect for a brush-up on the basics or as an everyday desk reference on the job, this is the reliable little book you can always turn to for answers. Get a quick and thorough intro to the basic concepts of coding with JavaScript Review what you've already learned or pick up essential new skills Add interactive features to websites with JavaScript programming Keep this concise reference book handy for jogging your memory as you work This book is to the point, focusing on the key topics you need to know about this popular programming language. Great for supplementing classroom learning, reviewing for a certification, or staying knowledgeable on the job.
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)